Wikileaks subordinate: supremacy state in the system international contemporary (2013)
This article tries to demonstrate, using as example the WikiLeaks case that the State system is as b today as in the period of the International Classic system , starting with the premise that the State is rational and it is the only one with possibilities of achieving order in the face of disorder. In addition , in periods of crisis , due to clashes for the accumulation of power , it has the power to re-do the rules, despite the fact that the globalist speeches insist on minimizing its role in the contemporary international system.